2016
DOI: 10.1021/acs.jafc.6b04027
|View full text |Cite
|
Sign up to set email alerts
|

Residual Behaviors of Six Pesticides in Shiitake from Cultivation to Postharvest Drying Process and Risk Assessment

Abstract: The dissipation of six pesticides (carbendazim, thiabendazole, procymidone, bifenthrin, λ-cyhalothrin, and β-cyfluthrin) in shiitakes from cultivation to postharvest drying process was investigated, and the dietary exposure risk was estimated thereafter. The field trial study indicates that the half-lives of carbendazim, thiabendazole, and procymidone were much shorter than those of bifenthrin, λ-cyhalothrin, and β-cyfluthrin. Furthermore, the effects of two drying processes on the residues and processing fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The dosage of carbendazim, thiabendazole, and procymidone was applied at twice of the recommended dosage, while bifenthrin, λ ‐cyhalothrin, and β ‐cyfluthrin were applied at four times of the recommended dosage. The dosages of all six pesticides were the same as our previous study (Liu et al, ) and diluted in 5 L of distilled water and sprayed onto the ripe shiitake fruiting bodies using a JACTO‐HD sprayer. After spraying pesticides, approximately 40 kg shiitake samples at uniform maturity and size were randomly chosen for processing analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The dosage of carbendazim, thiabendazole, and procymidone was applied at twice of the recommended dosage, while bifenthrin, λ ‐cyhalothrin, and β ‐cyfluthrin were applied at four times of the recommended dosage. The dosages of all six pesticides were the same as our previous study (Liu et al, ) and diluted in 5 L of distilled water and sprayed onto the ripe shiitake fruiting bodies using a JACTO‐HD sprayer. After spraying pesticides, approximately 40 kg shiitake samples at uniform maturity and size were randomly chosen for processing analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The dissipation behavior and residue of methoxyfenozide have been further revealed through open field trials. Furthermore, a risk assessment was carried out based on the risk quotient (RQ) method, 24,25 also known as the hazard quotient (HR) method. 26 This study not only contributes to establishing a reasonable Chinese MRL for methoxyfenozide but also provides practical data on its safe use.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations and characteristics of pesticide residues in food are altered during processing. Numerous studies have shown that food processing can contribute to pesticide dissipation [9,18,19]. However, few studies have been reported on the changes in pesticide residues during CHM processing.…”
Section: Resultsmentioning
confidence: 99%